Reconnection rate and multi-scale relativistic magnetic reconnection driven by ultra-intense lasers. (23rd June 2021) - Ping, Yongli; Zhong, Jiayong; Wang, Xiaogang; Zhao, Gang; Li, Yutong; He, Xian-Tu
Abstract: The reconnection rate in relativistic magnetic reconnection driven by two relativistic intense femtosecond laser pulses is investigated using three-dimensional particle-in-cell (PIC) simulation. As the drive is enhanced, the current sheet is narrowed, and the reconnection rate is weakened. A new theoretical model is given to explain the rate observed in the PIC simulation. In addition, multi-scale reconnection is studied by setting a different ion mass in the simulation code. For m i = 1836 m e, the current sheet is only at the electron scale, and only electron outflow jets are observed, which are super ion Alfvénic and close to the electron's Alfvénic speed. The lengths of the electron outflow jets reach 100–200 times the length of the electron gyroradius and beyond the ion gyroradius. However, when m i = 100 m e, more ions are coupled to electrons during the laser and plasma interaction, there are also electron outflow jets and no ion outflow jets in the current sheet, and the electron outflow jets are embedded in a wider ion-scale current layer.